ANALYSIS OF THE EFFECT OF PROMOTION, DISCOUNT, AND BRAND TRUST ON PERFUME PRODUCT PURCHASE DECISIONS IN SURAKARTA - Ellyco Onny Pamungkas; Suhesti Ningsih; Muhammad Cholis; Hadi Samanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study aims to analyze the influence of promotion, discounts, and brand trust on purchasing decisions for perfume products in Surakarta. The background of this research is based on the increasingly competitive perfume industry, where businesses are required to implement effective marketing strategies to attract consumers and maintain market competitiveness. This research employed a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 100 respondents who had previously purchased perfume products in Surakarta. The sampling technique applied in this study was accidental sampling. Data analysis was conducted using multiple linear regression. Among the three independent variables, brand trust was identified as the most dominant factor influencing purchasing decisions, with the highest regression coefficient value of 0.56. Several statistical tests were also carried out, including classical assumption tests, partial t-tests, and coefficient of determination tests. The results of the study indicate that promotion, discounts, and brand trust each have a positive and significant effect on purchasing decisions. Furthermore, the coefficient of determination test showed an Adjusted R Square value of 0.885, which means that 88.5% of the variation in purchasing decisions can be explained by promotion, discounts, and brand trust, while the remaining 11.5% is influenced by other factors outside the scope of this study. In conclusion, promotion, discounts, and brand trust are important factors that should be considered by perfume business owners in developing effective marketing strategies to improve consumer purchasing decisions in Surakarta.